Differentiation of Extracted Gelatins from Porcine, Bovine and Chicken Origins Based on their Physical, Chemical and Structural Properties using Analytical Techniques (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Physicochemical properties of extracted gelatins from porcine, bovine and chicken sources compared to that of commercial bovine and porcine gelatins have been determined. Gelatin samples were assessed for their pH, water holding capacity, fat binding capacity, foaming capacity and stability, structural properties, thermal and amino acid profiles and molecular weight distribution. There were significant differences (P
Keywords: Gelatin; Physicochemical properties; Functional group; Structural properties; Thermal profiles